Attitudes of University Lecturers towards Students’ Evaluation of the Teaching Process - Davidović Rakić, Jelena I.; Kostić, Senka M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The objective of ​​the paper was to examine the attitudes of university lecturers towards evaluation of the teaching process by students. In addition, we were interested in whether there is an effect of an academic title (assistant, assistant professor, associate, and full professor) or years of work experience on the nature of that attitude. In order to investigate this, we constructed a scale of attitudes. The scale was separated in three dimensions: Invariability of student’s role, Indication of the limitations of evaluation, and Student incompetence in evaluation. The survey was conducted on a total of 287 university lecturers. The results showed that lecturers have a moderate to slightly positive attitude towards the evaluation on all three dimensions. Additionally, the lecturers with more years of experience exhibited a more negative attitude on the dimension of Invariability of student role in relation to the lecturers with less than 5 years of work experience. There were no differences between teaching assistants and senior lecturers (assistant, associate, and full professors) in the attitude about the evaluation of the teaching process by students. The results obtained in this way are in unison with the results of previous research and suggest that on the one hand, lecturers see positive aspects of evaluation in the form of active involvement of students in the teaching process, but on the other hand there is no confidence in the evaluation (negative side of evaluation) and the objectivity of the evaluation process itself.